Literature Study: Problems of Learning Evaluation in Achieving Educational Goals in the 2013 Curriculum Era - Mardiah Astuti; Bintang Wulandari; Khoirina Indah Sari; Nabila Nabila; Anggun Nadiya (Universitas Pahlawan Tuanku Tambusai, 2023)
Educational institutions and teachers face challenges and increasing demands, especially to prepare students for different situations and changes faster. Changes that occur are related to the development of science and technology. In this case, researchers have conducted descriptive research using qualitative methods. The data collection technique used in this study is adjusted to the purpose of this study, namely library research or literature study. This study uses data sources from relevant documents such as books, journals, or scientific articles related to the chosen topic. According to the Ministry of Education and Culture, the 2013 curriculum is a national curriculum program since 2013 or 2014. And the 2013 curriculum is a federal curriculum program that has been developed over the years and has fulfilled two dimensions of the curriculum, namely plans and arrangements regarding objectives, content, and learning materials, as well as the ways used for learning activities (Ministry of Education and Culture, Curriculum 2013). Learning evaluation is a series of processes or activities carried out systematically, the purpose of which is to obtain Information about educational activities that have been completed. Education aims to educate the nation's life through quality education so that individuals become more independent and master specific skills, beliefs, etc. The 2013 curriculum is a national curriculum program developed so far that meets two curriculum dimensions: planning and goal setting, learning content and materials, and learning activity methods.